Mengungkap Praktik Akuntabilitas Dalam Pelaksanaan Upacara Pembangunan Rumah Adat “Take Koke” Pada Masyarakat Desa Ratulodong Kabupaten Flores Timur - Emanuel Antonius Wuri Koten; Khojanah Hasan; Endah Puspitosarie (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
Take Koke activity is an activity of building a Traditional House which is part of a community tradition that generally requires accountability for every activity, especially in terms of financial management. This paper aims to understand how accountability is in community activities in Ratulodong Village, East Flores Regency. This study uses a qualitative approach with descriptive analysis. The results of the study indicate that the Take Koke activity committee has implemented the principle of accountability well, starting from the planning, implementation, to accountability stages. In planning activities, the committee holds a meeting to discuss the details of the implementation and the budget required. While at the implementation stage, the management records all income and expenses that occur in the Take Koke activity.